2000
DOI: 10.1007/s100510050010
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of zig-zag ladders

Abstract: We analyze the phase diagram of a system of spin-1/2 Heisenberg antiferromagnetic chains interacting through a zig-zag coupling, also called zig-zag ladders. Using bosonization techniques we study how a spin-gap or more generally plateaux in magnetization curves arise in different situations. While for coupled XXZ chains, one has to deal with a recently discovered chiral perturbation, the coupling term which is present for normal ladders is restored by an external magnetic field, dimerization or the presence o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
124
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(132 citation statements)
references
References 67 publications
6
124
1
1
Order By: Relevance
“…These nonvanishing averages indicate that the ground state breaks a Z 2 symmetry and has a vector chiral long-range order. Since κ (1) l and κ (2) l have the same sign and satisfy Eq. (6), the spin current J n κ (n) l flows as depicted in Fig.…”
Section: A Bosonization Approach For |J1| ≪ J2mentioning
confidence: 99%
See 1 more Smart Citation
“…These nonvanishing averages indicate that the ground state breaks a Z 2 symmetry and has a vector chiral long-range order. Since κ (1) l and κ (2) l have the same sign and satisfy Eq. (6), the spin current J n κ (n) l flows as depicted in Fig.…”
Section: A Bosonization Approach For |J1| ≪ J2mentioning
confidence: 99%
“…The ground state manifold has extensive degeneracy at the phase boundary J 1 /J 2 = −4. 37,38 In magnetic field the spins order with a helical magnetic structure s l /s = (sin θ c cos φ c l , sin θ c sin φ c l , cos θ c ) (2) in the classical limit (s = |s| ≫ 1), with a pitch angle…”
Section: Introductionmentioning
confidence: 99%
“…9 For the parameter range −4J 2 < J 1 < 0 of our main interest, Chubukov 6 suggested that the ground state just below the saturation field should be a nematic state made up of bound magnon pairs with a commensurate total momentum k = π if −2.67J 2 < J 1 < 0 (2.67 ≈ 1/0.38) and with an incommensurate momentum k < π otherwise, which was partly verified by mean-field theory, 10 numerical study, 11 Green's function analysis which fixed the commensurate-incommensurate transition point to J 1 /J 2 = −2.66908 (= −1/0.374661), 12 and weak-coupling bosonization analysis. 4,11,13 While earlier calculations of the ground-state magnetization process suggested metamagnetic transitions, 10,14 recent densitymatrix renormalization group (DMRG) study 11 finds that the total magnetization of finite-size chains changes by ∆S z = 2 at J 1 = −J 2 , ∆S z = 3 at J 1 = −3J 2 , and ∆S z = 4 at J 1 = −3.75J 2 below saturation, implying that the magnetization curve is continuous in the thermodynamic limit. 13 To reveal how the fully polarized FM state collapses into new states with decreasing either magnetic field or the coupling ratio |J 1 |/J 2 , we analyze magnon instability in the fully polarized state.…”
mentioning
confidence: 99%
“…4,11,13 While earlier calculations of the ground-state magnetization process suggested metamagnetic transitions, 10,14 recent densitymatrix renormalization group (DMRG) study 11 finds that the total magnetization of finite-size chains changes by ∆S z = 2 at J 1 = −J 2 , ∆S z = 3 at J 1 = −3J 2 , and ∆S z = 4 at J 1 = −3.75J 2 below saturation, implying that the magnetization curve is continuous in the thermodynamic limit. 13 To reveal how the fully polarized FM state collapses into new states with decreasing either magnetic field or the coupling ratio |J 1 |/J 2 , we analyze magnon instability in the fully polarized state. We apply a large enough magnetic field h such that the fully polarized state is the unique ground state for −4J 2 < J 1 < 0, and all multi-magnon excitations have positive excitation energies which decrease as h is reduced.…”
mentioning
confidence: 99%
“…It is deserved to mention here that this gap could also survive even for J 1 ≫J 2 ,J 3 , in which the system can be seen as the three free spin chains with intra-chain couplings J 1 perturbed by relevant perturbations generated by the inter-chain couplings J 2 and J 3 , as in the case of spin ladders [24][25][26] . Therefore, this case as well falls into the gapped phase.…”
Section: Bosonization and Low-energy Effective Theorymentioning
confidence: 99%